HUBUNGAN LARANGAN MEROKOK DI RUMAH DENGAN KEBERHASILAN BERHENTI MEROKOK - Ramadhan, Kadar (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2017)
The Global Adult Tobacco Survey (GATS) in 2011 indicated that despite the intention of tobacco user to cease smoking, only a few people that succeed to stop the smoking habit. This research aimed to investigate correlation between smoking bans at home and smoking cessation. The GATS design was a cross-sectional study. Resident ≥ 15 y.o as the target population and as much as 8.305 respondents were recruited by stratified multistage cluster sampling (4 stages) and only 1.376 respondent who had tried to quit smoking were chosen as the sample and being analyzed. The dependent variable was the achievement of smoking cessation. The descriptive statistic was reported in weighted proportions. Logistic regression analysis and adjustment for confounders were applicated. Smoking bans at home increased the odds of smoking cessation achievement by 200 % (OR: 2,0; 95%CI 1,1-3,4) compared to the inexistence of such rule at home. As a conclusion, smoking bans at home was able to increase the smoking cessation achievement in the stop smoking program.